A life-skills intervention programme addressing the selfconcept of Afrikaans-speaking youth offenders - Wicomb, Priscilla Zenobia (Stellenbosch : Stellenbosch University, 2008)
Thesis (MEdPsych (Educational Psychology))--Stellenbosch University, 2008.